Pengaruh Motivasi Kerja, Pendidikan, Etos Kerja, Pengembangan Sumber Daya Manusia dan Fasilitas Terhadap Produktivitas Kerja Pegawai Badan Pendapatan Daerah Kabupaten Muara Enim - Nopiyanti, Tri; Hamid, Abdul; Fitriya, Fitriya (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
The author carried out the research to know and analyze the influence of work motivation, education, work ethic, and development of human resources and facilities, individually and collectively, on the work productivity of employees of the Regional Revenue Agency of Muara Enim Regency. The research method used in this study is quantitative, using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, and normality test. The descriptive and inferential analysis used statistical calculations with multiple regression formulas, partial test simultaneous test, and the coefficient of determination. The research results showed that work motivation significantly affected the work productivity of Muara Enim Regency Regional Revenue Agency employees. Education significantly affects the work productivity of Muara Enim Regency Regional Revenue Agency employees. Work Ethic significantly affects the work productivity of Muara Enim Regency Regional Revenue Agency employees. Human Resource Development significantly affects the work productivity of Muara Enim Regency Regional Revenue Agency employees. Facilities significantly affect the work productivity of Muara Enim Regency Regional Revenue Agency employees. Work Motivation, Education, Work Ethic, Human Resource Development, and Facilities significantly affect the work productivity of Muara Enim Regency Regional Revenue Agency employees.